Decreasing incidence of type 2 diabetes mellitus in the United States, 2007–2012: Epidemiologic findings from a large US claims database. (July 2016) - Weng, Wayne; Liang, Yuanjie; Kimball, Edward S.; Hobbs, Todd; Kong, Sheldon X.; Sakurada, Brian; Bouchard, Jonathan
Abstract: Aims: To explore epidemiological trends in type 2 diabetes mellitus (T2D) in the US between 2007 and 2012 using a large US claims database, with a particular focus on demographics, prevalence, newly-diagnosed cases, and comorbidities. Methods: Truven Health MarketScan® Databases were used to identify patients with claims evidence of T2D in the years 2007 and 2012. Newly-diagnosed T2D was characterized by an absence of any T2D claims or related drug claims for 6 months preceding the index claim. Demographic and comorbidity characteristics of the prevalent and new-onset T2D groups were compared and analyzed descriptively for trends over time. Results: The overall prevalence of T2D remained stable from 2007 (1.24 million cases/15.07 million enrolled; 8.2%) to 2012 (2.04 million cases/24.52 million enrolled; 8.3%), while the percentage of newly-diagnosed cases fell dramatically from 2007 (152, 252 cases; 1.1%) to 2012 (147, 011 cases; 0.65%). The mean age of patients with prevalent T2D was similar in 2007 (60.6 y) and 2012 (60.0 y), while the mean age of newly-diagnosed T2D patients decreased by 3 years from 2007 (57.7 y) to 2012 (54.8 y). Hypertension and hyperlipidemia were the most common comorbidities, evident in 50–75% of T2D patients, and increased markedly from 2007 to 2012 in both prevalent and new-onset T2D populations. Cardiovascular disease decreased slightly in prevalent (−0.9%) and new-onset (−2.8%) cases. Conclusions: This large US health claims database analysis suggests stabilization in prevalence and declining incidence of T2D over a recent 5-year period, a downward shift in age at T2D diagnosis, but increases in several comorbidities.